Reliability Assessment of some Selected 11 kV Feeders within Ibadan Distribution Network - Abraham Olaide Amole; Muniru Olaide Olaide Okelola; Gabriel Olaide Amole (Universitas Ahmad Dahlan, 2020)
The energy satisfaction that consumers can obtain from the central grid solely depends on how reliable the feeder to which such customers are connected, simply because the reliability of both generation and transmission is not enough to guarantee adequate and secure energy delivery. It is on this premise that this paper employed load point reliability indices to assess selected feeders within the Ibadan electricity distribution network. The required data for this analysis was collected from the Ibadan Electricity Distribution Company, at Ring Road, Ibadan, the collected data captured the total number of faults, total fault duration, and total operating time from 2016 to 2019. The load point reliability indices used as performance metrics include Failure Rate (FR), Mean Time Between Failures (MTBF), Mean Time to Repair (MTTR), Availability Factor (AVF), and Maintainability (M). An adequate comparison of each of these indices on each feeder was made for the period of investigation. It was discovered that many of these feeders were not reliable. Therefore, the need to carry out extensive maintenance on these feeders is non-negotiable. Also, the result of this analysis will help the Distribution Company (DisCo) to make informed decisions that will accelerate the reliability of these 11kV feeders across the investigated region.